SUPER MARKETING - PATIL BHAGYASHRI; ADASUL MADHURI; MOGANE KAJAL (International Journal of Innovations in Engineering Research and Technology, 2021)
This project offers completely computerized process. By this system we can do completely paperless work. The newly created computerized system will maintain all the records of purchase, sales transaction. It also maintains details of orders, sailing, buying with accuracy and high speed. It maintains all records properly. This system shows various reports as like sales information, order details. This system minimizes workload, calculation and manpower. On the other side it saves lots of time. This software is developed using most advanced software development tool “Microsoft VB.Net” as front-end tool and “MS-Access” as back-end tool.